Violence all around - Sifton, John (Harvard Univ. Press, 2015)
Preface -- Deeds -- The desert of the real -- Continent and conquest -- Violence and distance -- The limits of remote violence -- Words -- The theater of force -- Defining violence -- Torture -- The violence of nonviolence -- Outrage -- Terror as justice -- Change -- Notes -- Acknowledgments -- Index